Monthly maps of sea surface dissolved inorganic carbon in the North Pacific: Basin‐wide distribution and seasonal variation. Issue 8 (6th August 2013) - Yasunaka, Sayaka; Nojiri, Yukihiro; Nakaoka, Shin‐ichiro; Ono, Tsuneo; Mukai, Hitoshi; Usui, Norihisa
Abstract : [1] We produced 84 monthly maps of sea surface dissolved inorganic carbon (DIC) concentration for the North Pacific from 2002 to 2008. The estimated DIC concentration agrees well with DIC concentration observed from research vessels at fixed time series stations (root‐mean‐square error of 10.2 μmol kg −1 ). The spatial distribution of 7 year annual mean DIC concentration corresponds to the sea surface salinity distribution and ocean circulation. We explored DIC seasonal variation by categorizing the North Pacific into 10 areal clusters. DIC decrease from March to July was captured: more than 120 μmol kg −1 in the northwest, but less than 40 μmol kg −1 in the subtropics. After subtracting the effects of air‐sea CO2 flux and salinity change, the residual DIC decrease from March to July can be considered as net community production (NCP): more than 14 mmolC m −2 d −1 in the boundary region between the subtropics and the subarctic extending from east coast of Japan to the date line, more than 8 mmolC m −2 d −1 in the coastal region of the subarctic, and 4–8 mmolC m −2 d −1 in the offshore region of the subarctic. The NCP corresponds well to 20–30% of the satellite‐derived net primary production. Key Points: Monthly maps of sea surface DIC are produced in the North Pacific Annual mean DIC distribution corresponds to salinity and ocean circulation DIC decrease from winter to summer indicates net community production